Acoustic Correlates To Contrastive Tone Heights In Two African Languages - Oakley, Madeleine (My University, 2021)
Languages with contrastive tone may phonetically realize tonal distinctions through changes in F0, relative F0, and vowel duration, amongst other cues (Abramson 1979; Zhang 2001; Levi 2005; Brunelle & Kirby 2016; Yu 2010). It has been argued that there is a universal correlation between vowel duration and F0, where H tones correspond to short vowels, and L tones correspond to long vowels (Abramson 1979; Dreher & Lee 1968; Gandour 1977). This pilot study expands the study of acoustic correlates of tonal contrasts by examining the interaction of pitch and duration in two understudied African languages: Nobiin and Guébie. The pilot study results do not show evidence for a negative correlation between pitch and vowel duration, suggesting this presumed universal correlation may be language (or even speaker) specific. Furthermore, the acoustic correlates to tone are independent of the phonological inventories of Nobiin and Guébie, which has implications for the phonetics/phonology interface.
Keywords: HUMANITIES and RELIGION::Languages and linguistics::Other languages::African languages; Acoustic correlates; contrastive tone heights